Reinterpretasi Makna Hijrah dan Implikasinya terhadap Moderasi Beragama: Aplikasi Maʿnā cum Maghza pada Q.S. Al-Nisāʾ: 100 - Al Chudaifi, Muhammad Abdul Rohman; Muliana, Siti (UIN Sunan Kalijaga Yogyakarta, 2021)
This article focuses on the word hijrah in Q.S. al-Nisāʾ: 100. It is an important topic following the rise of the hijrahmovement along with all its religious attitudes. This development led to a semantical shift of the word hijrah, from originally referring to the historical movement of the Prophet Muhammad (peace be upon him) in 622 AD to a kindlifestyletyle marked with symbolic and exclusive religiousness. To this end, the study used the Maʿna cum Maghza method of interpretation. This article argues the followings: First, the current hijrah trend with all its dynamics undergoes a shift in meaning so that it is closer to symbolic religiosity. Second, the historical-phenomenal significance of QS. al-Nisāʾ: 100 is that the hijrah movement in Indonesia should be seen within a proportional context of its historical, ideological and cultural basis, especially for the context of Indonesia which has a diversity of tribes, races and religions. Third, the trend of hijrah with its exclusive religious attitude slowly but surely must be addressed by advocating pluralism values. Thus, inclusiveness and openness are needed as the main foundation in building a plural and religious moderation.